The Effectiveness of Topical 5-fluorouracil Treatment on Mouse Skin Squamous Cell Precancerous Lesions through Caspase-3 Expression - Nurkasanah, Siti; Hoemardani, Aida S.D.; Sinuraya, Evlina Suzanna; Wuyung, Puspita Eka (Indonesian Journal of Cancer Chemoprevention, 2022)
Skin cancer is a disease that develops in the epidermis of the skin and can be invasive, such as squamous cell carcinoma (SCC). Early detection of squamous cell precancerous can prevent these lesions from progressing to invasive SCC and increase the effectiveness of therapy. 5-fluorouracil (5-FU) is an antimetabolite compound as a pyrimidine DNA/RNA antagonist molecule that induces cell apoptosis. The main objective of this study was to evaluate the effectiveness of the topical 5-FU cream (Dharmais NCH) compared to imiquimod 5% on apoptosis through the expression of caspase-3 in precancerous squamous cells of mouse skin induced by 7,12-dimethylbenzen[a]-anthracene (DMBA)/croton oil treatment. This research assess three differences concentration of 5-FU include 1%, 2%, and 5% on 24 wild type mouse divided into 6 groups including positive control (with carcinogenesis but without treatment), negative control (without treatment; normal), carcinogenesis with treatment 5-FU cream (1%, 2%, and 5%) or 5% imiquimod cream. Two-stages carcinogenesis induced by DMBA and followed by croton oil. The expression of caspase-3 was analyzed using immunohistochemistry. Statistical analysis was performed by one-way ANOVA using SPSS version 23. The induction of two-stages of carcinogenesis (weeks 1 to 10) caused papilloma lesions on the skin of mouse. Furthermore, 5-FU treatment for 4 weeks (weeks 11 to 14) showed a decrease in the cumulative number of papillomas (p<0.05) and immunohistochemical analysis showed caspase-3 expression on 5-FU treatments (1%, 2%, and 5%) was not significantly different from the imiquimod treatment (p>0.05). The apoptotic effect of 5-FU treatment on precancerous skin squamous cell lesions in mouse was not significantly different from the standard treatment using imiquimod. This suggests that 5-FU treatment has potential as a future therapy in squamous cell precancerous skin lesions.Keywords: 5-fluorouracil, caspase-3, squamous cell precancerous, skin, topical treatment.